The Olympic athlete as a role model in a skill program to affect the attitudes of the school children - Παπαδοπούλου, Σοφία (Πανεπιστήμιο Πελοποννήσου, 2017)
This research is based upon the experience, knowledge and skills which the author as an Olympic athlete has achieved and concentrated on through all the stages of her life path. The author had strongly in her mind the desire to recombine all her knowledge and create a useful“instrument” for all the primary physical education society, teachers and pupils. Her experience is a life timestruggle, since her childhood to reach the Bronze Olympic medal in the sport of sailing, at Beijing 2008.The author will be asking the following question: “Can an Olympic athlete either as a physical educator, or/an assistant physical educator affect positively the attitude quality of elementary school children?” The methodology of this research spins around this question and involves three procedures: questionnaires, interviews and a pilot program of a new sport sailing plan. The questionnaires and the interviews, which follow in the next pages, examine the relative thoughts and beliefs of the Olympians and her sports and education officials. The sailing pilot program provides us with a practical, experiential perspective. The results of this thesis survey demonstrate that, indeed, the abilities, skills and motor skills of the Olympic athlete must be combined together with scientific and technical knowledge and afterwards they have to be inserted within the context of the physical education system. Thus, this project presents an initiative that is based on sound philosophical-theoretical pedagogical principles and applied in a practical way, thus enhancing an understanding of contemporary physical education science.
Keywords: Physical education and training -Greece; Physical education for children - Greece; Olympics - Philosophy; Φυσική αγωγή και εκπαίδευση - Ελλάδα; Φυσική αγωγή για παιδιά - Ελλάδα; Ολυμπιακοί αγώνες - Φιλοσοφία; Sport education; Olympic educational program; Olympic Athlete; Olympism; Sailing project